THE EFFECTIVENESS OF THE KPK IN HANDLING MILITARY CORRUPTION CASES WITH THE GENERAL PUBLIC BASED ON LEGAL CERTAINTY - Napitupulu, Marina Raisa T; Wijaya, Soma; Takariawan, Agus (Awang Long Law Review, 2024)
This research discusses how the KPK's authority in investigating corruption crimes when committed by the general public and members of the military and whether the KPK's authority as an investigator in handling corruption crimes committed by the general public and members of the military can be carried out effectively. By using normative research methods, this study found that the regulations relating to the investigation of corruption crimes committed by the general public and members of the military overlap and become very complex. So that to reduce this dynamics and complexity, it is necessary to be firm on several rules that have been regulated and promulgated.